Polish participants in the Varna expedition - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 1997)
The article constitutes an attempt to establish the personal composition of the Polish participants in the Varna expedition of 1443–1444. The author analyzes the problem of identifying the individuals accompanying King Władysław III Varnenčik during the anti-Turkish campaign and the Battle of Varna itself. The aim of the study is to reconstruct the fullest possible list of participants in the expedition on the basis of documentary and narrative sources. This topic is of considerable importance for research into the organization of the campaign, the participation of the Polish knighthood in the struggle against the Ottomans, and the functioning of the royal court during wartime. The author makes use of royal chancery documents, privileges, correspondence, chronicles, and accounts, above all the Annals of Jan Długosz. The article demonstrates that it is possible to identify approximately one hundred individuals who participated in the expedition or were connected with the royal entourage in 1443–1444. Documentary evidence, such as royal grants and records issued in Buda, Oradea, or during the army’s march, is of particular importance. The author also points to methodological difficulties resulting from the fragmentary nature of the sources. Some participants do not appear in the records because they left the expedition before the Battle of Varna or were not explicitly attested in the documentation. The results of the analysis indicate that the reconstruction of the expedition’s personnel remains provisional, yet it allows for a better understanding of the socio-political background of Władysław Varnenčik’s last crusade.